Internet addiction and sleep disturbance symptoms among Turkish high school students. Issue 3 (7th August 2013) - Canan, Fatih; Yildirim, Osman; Sinani, Gjergji; Ozturk, Onder; Ustunel, Tuba Yildirim; Ataoglu, Ahmet
Abstract: We aimed to examine the correlation between Internet addiction and sleep disturbance symptoms among students. Internet Addiction Test (IAT) was used. The students with addictive Internet use were more likely to have difficulty in falling asleep and night awakenings. Problematic Internet users and addictive Internet users were found to sleep significantly less than avarage Internet users. A significant positive correlation between daily sleep duration and IAT and weekly Internet use was found. Linear regression analysis revealed a significant negative and independent association of IAT with daily sleep duration. These results indicate an association between the Internet addiction and impaired sleep.